Knowledge, Attitudes, and Practices regarding Chickenpox Disease and its Prevention in Singapore: Comparison between Parents and Medical Students - Ernest Weisheng Ho MBBS; Imelda Lustestica Ereno DPPS, DPSMID; Masitah Ibrahim MRCPCH (UK), MCI (NUS); Cheo Lian Yeo MMED (PAED), FAMS (Proceedings of Singapore Healthcare, 2012)
Introduction: The incidence of chickenpox in Singapore is steadily increasing despite the availability of effective preventive measures. To address the need for improvement in public education, a survey was conducted to establish if differences exist amongst parents and medical students with regards to their knowledge, attitudes, and practices regarding chickenpox and its prevention. Methods: Over a six-week period in 2010, an online survey involving parents who attended a paediatric clinic, and medical students from the National University of Singapore, was conducted. Results: Parents had a significantly greater lack of knowledge compared to medical students ( P <0.001). Family and friends were the main source of information for parents and junior medical students, unlike senior medical students who learnt more from physicians. A large majority of responders (85.2%) favoured vaccination for varying reasons, with parents and junior students being more concerned about the spread of disease and favouring its avoidance, and senior students fearing life-threatening complications. Parents who would not recommend the vaccine considered chickenpox a rite of passage and believed the vaccine lacks long-term benefits, while a perception that the disease is mild was more prevalent among medical students. A better understanding of the disease and vaccine was the most influential factor for changing decisions against vaccination. Conclusion: Greater efforts to disseminate information about chickenpox disease and its prevention are needed to address important deficits in public health and medical school education. Being aware that chickenpox can be more than just a mild disease with serious complications may increase the uptake of chickenpox vaccination.